استخدام الـSBS(Styrene Butadien Styrene) في تعديل البيتومين المستخدم في تصميم الخلطات البيتومينية - مرشد, ديانه عادل (Latakia University Journal -Engineering Sciences Series, 2016)
أجري هذا البحث بهدف تحسين خواص الخلطة البيتومينية وتحسين الممانعة الحرارية لطبقة التغطية السطحية من الرصف اللين, حيث يتعرض البيتومين إلى مجموعة من التغيرات، تبدأ من مرحلة إنتاج المجبول البيتوميني في درجات حرارة مرتفعة، وتستمر هذه التغيرات إلى مرحلة استثماره. وقد استخدم البيتومين المعدل بالبولمير، لتحسين أداء الرصف البيتوميني في مجالات عديدة، وفي بحثي هذا عملت على تعديل البيتومين المحلي، بإضافةSBS بحيث يستخدم البيتومين المعدل لتصميم خلطات بيتومينية محققة لشروط تصميم الخلطة البيتومينية، ويحسن من مقاومتها للحرارة. تم تحديد خواص البيتومين غير المعدل والبيتومين المعدل بالـSBS بنسبة 3.5%, وذلك من خلال سلسلة من التجارب قبل وبعد اختبار الفاقد بالحرارة, وتم تحديد خواص الحصويات المستخدمة, وتم تصميم خلطات بيتومينية، باستخدام البيتومين60-70 والبيتومين المعدل بالـSBS, بالمقارنة بين النتائج فإن الـSBSأدى إلى زيادة قساوة البيتومين، التي تظهر من خلال انخفاض الغرز والاستطالة المترافقة بارتفاع بقيمة درجة حرارة التميع,كما تحسنت قيمة النقص في الثبات بنسبة15% وهذا ينعكس بدوره على ممانعة أكبر لدرجات الحرارة المرتفعة, وبالتالي تحسن في مقاومة هذه الخلطات المعدة من بيتومين معدل تجاه التأثير الحراري الذي تتعرض له. This research was performed to improve the quality of Bituminous mixes, and improve the thermal resistance of the surface bituminous layer, the bitumen has a various changes, that which begins from the production of the bituminous mixture in high temperatures, these changes continues to the phase of it's use. For this purpose, SBS(Styrene Butadien Styrene) was selected to be an improving material to bitumen according to the rate: 3.5% for SBS.in my research I work on modifying the local bitumen by adding the SBS so that the modified bitumen can be used to design bituminous mixes within the limits of bituminous mixes designed specifications, and improve it's thermal resistance. some experiments were held to determine the qualities of the modified and unmodified bitumen,befor and after Lose Of Heating, the results were within the specifications 'limits. According to Marshal's method, samples of Bituminous mixes were prepared for all Bituminous sorts used in our research. These samples were put under required tests, and samples were prepared according to an ideal rate of Bitumen. the result was the Bitumen modified by adding SBS improve the quality of Bitumen to thermal resistance.